Persepsi Wisatawan Domestik Terhadap Layanan Bandung Tour on Bus (BANDROS) - Yudi Satriadi; Nurul Syamsiah; Wiwin Yuliani (STIEPAR YAPARI Bandung, 2022)
This study aims to determine and understand the perceptions of domestic tourists on the service quality of Bandung Tour on bus (Bandros), which is one of the tourism products in Bandung. Bandros is a tour bus provided by the Bandung city government and is intended for tourists who want to get around the city of Bandung. The research data uses a questionnaire filled out by tourists who have taken Bandros tours. The number of respondents as the study sample was 115 people determined using accidental sampling technique. The quality of Bandros services studied consists of 5 dimensions, namely the dimension of reliability, responsiveness dimension, assurance dimension, empathy dimension, and tangible dimension. Measurements are made using a Likert scale to make it easier to compile descriptions and interpret the variables being studied, as well as process data using descriptive statistical methods. Descriptive statistical processing in this study uses the calculated average value as a reference for determining the classification category of the assessment. From this study it is concluded that the overall perception of domestic tourists on the quality of Bandros services is in the good category.